1993
DOI: 10.1002/jcp.1041570311
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of tumor necrosis factor on LLC‐PK1 transepithelial resistance

Abstract: Renal epithelial LLC-PK1 cell sheets incubated with tumor necrosis factor (TNF) undergo an acute, spontaneous, and rapidly reversible decrease in transepithelial resistance (TER). (Mullin et al., 1992). However, 24 to 72 h following TNF exposure, TER across the cell sheet increases 2-fold. This later effect of TNF is also reversible, albeit slowly. The TER of TNF-treated cell sheets then declines toward initial levels between 72 and 144 h following exposure to the cytokine. Whereas the long-term increase in TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 37 publications
(43 reference statements)
2
11
0
Order By: Relevance
“…In addition, treatment with infliximab (anti-TNF) has been reported to restore barrier function in CD, and some UC, patients [51][53]. However, conflicting studies exist regarding the interpretation of the effects of TNF that may reflect differences in the specific epithelial cell line used or variations in the dose and length of the treatment with TNF [54]. For example, in the intestinal epithelial cell line, Caco-2, TNF stimulation results in a delayed effect on permeability by increasing small molecule flux within 24 hrs, but reduction in TEER is not observed until 48 hrs post treatment [55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treatment with infliximab (anti-TNF) has been reported to restore barrier function in CD, and some UC, patients [51][53]. However, conflicting studies exist regarding the interpretation of the effects of TNF that may reflect differences in the specific epithelial cell line used or variations in the dose and length of the treatment with TNF [54]. For example, in the intestinal epithelial cell line, Caco-2, TNF stimulation results in a delayed effect on permeability by increasing small molecule flux within 24 hrs, but reduction in TEER is not observed until 48 hrs post treatment [55].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several conflicting theories regarding the relationship between tight junction function and cell proliferation. Some investigators reported that a rise in cell number could generate an increase in TER (25)(26)(27)(28). However, contrasting reports suggested that overgrowth of cells could result in enhanced transepithelial permeability.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α increases permeability of bovine pulmonary artery endothelial (BPAEC) monolayers, human colonic adenocarcinoma (Caco-2), HT29/B6 and cholangiocytes, but decreased solute permeability of uterine epithelial cells (UECs) [47]. Further, TNF-α can either increase or decrease solute exchange depending on the type of insult in porcine renal epithelial cells (LLC-PK1) [48,49]. These effects are mediated by diverse mechanisms involving actin reorganization, monolayer motility, NF-kβ activation, apoptosis and reorganization of junctional proteins [49-54].…”
Section: Introductionmentioning
confidence: 99%